Lieu d’intimité – lieu d’imagination. Géographie littéraire de Zygmunt Krasiński - Markuszewska, Agnieszka (Studia Romanica Posnaniensia, 2023)
Zygmunt Krasiński, the most European of the Polish Romantic writers, composed many literary texts influenced by foreign travels. In his writing, specific geographical spaces were transformed at once into places of imagination and places of intimacy, forming a unique sphere of auto/bio/geo/graphy. This is especially noticeable in Krasiński’s poetic prose written in French, mainly in the half-private and half-literary travel impressions of his excursions in the Alps. The tension between a place of imagination and a place of intimacy is also reflected in the poet’s correspondence, which can be analysed as a textual form of interiorization of the strictly defined places. It is shown in the article on the examples of the Alps and Provence.